The capacitating talent in Industry 4.0 - Costa, Massimiliano (Formazione & insegnamento, 2018)
Industry 4.0 makes the more dynamic workers innovate by getting into action creativity and generative knowledge. The transformation/production process is mediated by technology and robotics nowadays. This process influences both the worker professional and identity process construction. The essay highlights how talent within industry 4.0 contexts grow out from two different dimensions crossing: practice, as continuous engagement and exercise and environment capability within working context, as a possibility to promote creativity, affectivity and unpublished solution creation, made by the workplace. So talent becomes a multimodal construct in which work practice exercise is the expression of understanding, exploring, evaluation of both freedom to achieve and take part in digital networks. These dimensions in Industry 4.0 turn the “to do” in a signification and project realization process, able to involve through agency the real operative context.